Faith, Culture, and Inequality: Healthcare Access Among Elderly Han Buddhist Monks in China - Zhenyu Liu; Chompoo Gotiram (Prosiding University Research Colloquium, 2026)
Elderly Han Buddhist priests continue to be overlooked, even though China's elderly population is expanding and presents substantial obstacles to equitable healthcare access. Previous research has not sufficiently examined how religious teachings, cultural practices, and socio-economic constraints interact to shape disparities in healthcare access within monastic communities. The objective of this investigation is to examine the impact of religious, cultural, and economic factors on the healthcare disparities and access of elderly Han Buddhist clergy in China. Using a mixed approach including a quantitative survey this study found that high levels of religiosity significantly hindered access to biomedical treatment, while internal cultural support within the monastic community enhanced access to healthcare. Access to medical services was also considerably enhanced by socio-economic factors, including urban location and education level. The theoretical discourse on faith-based health behavior and social capital in healthcare is enriched by these findings, which illustrate that the ideological component of structural exclusion of religious communities is not solely economic in nature. This research offers multidimensional policy implications, including inclusive health insurance schemes, training health workers sensitive to spiritual values, and empowering monastery-based health cadres. To develop sustainable healthcare solutions that align with the religious and cultural values of elder monastic communities, a collaborative, cross-sector approach is required, involving government, NGOs, and religious institutions.